Manajemen Humas dalam Lembaga Pendidikan: Strategi Komunikasi dan Penguatan Citra Sekolah di Era Digital - Hardiki, Dzulfikar; Sunhaji, Sunhaji (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse digital public relations management practices in strengthening the image of private schools in Cilacap Regency. The research uses a qualitative approach with a multi-site case study design in three schools, namely Raden Fatah Cimanggu Senior High School, Darussalam Karangpucung Vocational School, and Jenderal Ahmad Yani Karangpucung Senior High School. Data collection was conducted through in-depth interviews with 12 key informants, participatory observation for two months of digital public relations activities, and content analysis of 150 social media posts. The results showed that the implementation of a multi-platform digital public relations strategy was able to increase the effectiveness of school communication, as indicated by an average engagement rate of 30%, a reach of 6,167 users per week, a positive sentiment of 79%, and a reduction in crisis response time from 36–48 hours to 7–12 hours through the use of the school's official Instagram account. These findings confirm the effectiveness of digital public relations strategies that are in line with the theory of symmetrical two-way communication, and emphasise the importance of strengthening staff digital literacy and developing content based on local values in school public relations management.